Emerging role of transforming growth factor-β-regulated long non-coding RNAs in prostate cancer pathogenesis - Shree, Bakhya; Das, Koyel; Sharma, Vivek (Cancer pathogenesis and therapy, 2023)
Prostate cancer (PCa) is the most common malignancy in men. Despite aggressive therapy involving surgery and hormonal treatments, the recurrence and emergence of metastatic castration-resistant prostate cancer (CRPCa) remain a major challenge. Dysregulation of the transforming growth factor-β (TGF-β) signaling pathway is crucial to PCa development and progression. This also contributes to androgen receptor activation and the emergence of CRPC. In addition, TGF-β signaling regulates long non-coding RNA (lncRNA) expression in multiple cancers, including PCa. Here, we discuss the complex regulatory network of lncRNAs and TGF-β signaling in PCa and their potential applications in diagnosing, prognosis, and treating PCa. Further investigations on the role of lncRNAs in the TGF-β pathway will help to better understand PCa pathogenesis. [Display omitted] •Long non-coding RNAs (lncRNAs) regulate prostate cancer (PCa) pathogenesis.•LncRNAs act as effectors and regulators of the transforming growth factor-β (TGF-β) pathway in PCa.•The TGF-β pathway is closely related to androgen receptor (AR) signaling.•TGF-β-regulated lncRNAs are potential biomarkers and therapeutic targets for PCa.